Designing Mobility in a City in Transition. Challenges from the Case of Palermo - Vinci, Ignazio; Di Dio, Salvatore (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Transport policy is one of the most crucial sectors in the process of adaptation of contemporary cities to the challenge of sustainable development. For its close relation with social habits and people behaviors, in fact, innovation in transports play a strategic role both in the decreasing of the environmental impact of mobility and in the improvement of the quality of the built environment. To do so, however, cities need to reach a more effective integration between transport policy and land-use planning, as well as taking full advantage by the spreading of new technologies. In this context, this paper discusses the challenges provided by the reshaping of the transport system in the metropolitan area of Palermo, the second larger city in Southern Italy. It attempts to explore, particularly, the potential connections between the future “hard factors” of the transport policy – as a result of the programme of infrastructural improvement under realization in the urban area –, with other “soft factors”, such as the practices of social innovation in the field of mobility with the help of ICTs and other opportunities for urban regeneration linked to the reshaping of the transport system.